Evaluation of the extraction performance of commercial ground roasted coffee (@limentech, Ciencia y Tecnología Alimentaria, 2014)
The coffee extraction process can be defined as the operation by which hot water moistens roasted and ground coffee, dissolving the chemical compounds responsible for aroma and flavor. The objective was to evaluate the extraction process performance of commercially roasted coffee samples. The work was carried out in the Coffee Technology Laboratory at the University of Pamplona. Three commercial brands most consumed in the region were selected, and particle size and soluble solids analyses were performed. The grinding process was evaluated according to NTC 2421, and the extraction process performance was evaluated according to NTC 2442, in order to obtain the highest extraction of soluble solids in relation to particle size. Two methods were used to determine soluble solids in commercial coffee beverages: Direct drip method: for medium granulometry, NTC 4602-1 was applied and the Direct contact method: for coffee with coarse granulometry, NTC 4602-2; to determine the yield in each coffee maker used, the same conditions and variables were taken into account for each extraction method. The results obtained were analyzed by analysis of variance (ANOVA), with a degree of significance of 5%, establishing whether there were significant differences between the samples evaluated. It was concluded that the process conditions that influenced the extraction yield of the 3 samples evaluated were: the variation in particle size and the content of soluble solids in the extract.
Keywords: Diluted coffee; Extract; Particle size; Yield; Soluble solids